2022
DOI: 10.1007/s00216-022-04240-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping of mercury and selenium in mushroom fruit bodies with laser ablation–inductively coupled plasma-mass spectrometry

Abstract: This work describes the development of a novel method for quantitative mapping of Hg and Se in mushroom fruit body tissues with laser ablation coupled to inductively coupled plasma-mass spectrometry (LA-ICP-MS). Different parameters of the protocol for preparation of the standards used for quantification via external calibration were assessed, e.g., the dissolution temperature of gelatin standards and the addition of chitosan and l-cysteine as additives to the gelatin-based calibration droplets to better match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(83 reference statements)
0
4
1
Order By: Relevance
“…The value obtained with polymer films was close to the one of our previous study; no other LODs were reported for this element. For 78 Se, LOD of 0.1 µg.g -1 could be obtained with the polymer films with both normalization, which is slightly better than the one reported by Brauer et al with gelatin-cysteine microdroplets standards (0.3 µg.g -1 ) [21]. Additionally, this value is 10 times lower than the one we obtained in our previous study (1 µg.g -1 ) with He as collision gas [12].…”
Section: Polymer Film Methods Verification and Methods Comparisoncontrasting
confidence: 59%
See 2 more Smart Citations
“…The value obtained with polymer films was close to the one of our previous study; no other LODs were reported for this element. For 78 Se, LOD of 0.1 µg.g -1 could be obtained with the polymer films with both normalization, which is slightly better than the one reported by Brauer et al with gelatin-cysteine microdroplets standards (0.3 µg.g -1 ) [21]. Additionally, this value is 10 times lower than the one we obtained in our previous study (1 µg.g -1 ) with He as collision gas [12].…”
Section: Polymer Film Methods Verification and Methods Comparisoncontrasting
confidence: 59%
“…For Hg, LODs were around 0.3 µg.g -1 with MMS, which is much lower than what Debeljak et al obtained with Hgspiked embedding medium standards (4.9 µg.g -1 ) [29] and what Pozebon et al obtained (2.2 µg.g -1 ) [27]. However, low values of 0.04 µg.g -1 and even 0.006 µg.g -1 could be obtained with liver and gelatincysteine standards analysed by ICP MS/MS [22] [21]. To sum up, LODs for all elements were lower using the polymer film standards compared to MMS.…”
Section: Polymer Film Methods Verification and Methods Comparisonmentioning
confidence: 57%
See 1 more Smart Citation
“…Additionally, it can be combined with other technologies for superior detection efficiency. A new method for the efficient monitoring of the spatial distribution of Hg and Se in mushrooms (with a spatial resolution as low as 5 µm) was proposed for the first time, with researchers using laser ablation (LA) and ICP-MS to quantify mercury and selenium in mushroom substrates with detection limits of 0.006 and 0.3 µg•g −1 , respectively [32]. For accomplishing the simultaneous determination of trace selenium and cadmium in rice samples, G. Lan et al [33] first introduced bypass gas to modify graphite furnace electrothermal evaporation (GF-ETV) and ICP-MS.…”
Section: Common Fluorescence Spectroscopy Detection Methodsmentioning
confidence: 99%
“…Interestingly, Pb was only found in the first layer of the white and brown rice whereas Pb had penetrated the second layer in the parboiled rice. Braeuer et al 180 investigated the levels of Hg and Se in edible mushrooms in view of the health risks from Hg accumulation or potential health benefits from Se. Porcini mushrooms from three different species ( Boletus edulis , Boletus aereus and Boletus pinophilus ) and one parasol mushroom ( Macrolepiota procera ) were collected and analysed.…”
Section: Applications: Clinical and Biological Materialsmentioning
confidence: 99%